EVALUATION OF ELECTRIC CAR RESEARCH TRENDS THROUGH BIBLIOMETRIC ANALYSIS: A Literature Review - Lazuardy, Ardhy (International Journal Science and Technology, 2023)
Due to increasing environmental and sustainability concerns, electric cars have become a significant research focus in recent years. To understand the development and Impact of scientific research related to electric vehicles, a bibliometric analysis was carried out. This research collects data from Scopus, using the keywords "electric vehicle" OR "electric vehicles" OR "E.V." AND "product development." The results of the analysis show significant growth in the number of publications related to electric cars over the last few years. Analysis of publication trends identified periods of substantial growth and declining trends that may reflect changes in research focus. Specific journals and conferences were also identified as crucial platforms for research in this domain. Mapping of researcher collaborations and analysis of author contributions reveals a growing collaboration network within the electric car research community. Keyword analysis provides an in-depth look at dominant research themes, while citation analysis highlights works that have greatly influenced the field. This analysis provides valuable insight into the evolution of electric car research, identifying key trends, researcher collaborations, and the Impact of particular works. These findings can be used to guide future research and understand the rapid dynamics of developments in the electric car domain.